Clinical and Immunological Markers of Pulmonary Impairment Among People With HIV in India. (11th May 2022) - Baidya, Anurima; Sangle, Shashikala; Marbaniang, Ivan; Kulkarni, Vandana; Deshpande, Prasad; Nimkar, Smita; Chavan, Amol; Salvi, Sonali; Lokhande, Rahul; Kadam, Dileep; Gupta, Amita; Mave, Vidya; et al.
Abstract: Background: Despite antiretroviral therapy, chronic lung diseases remain an important source of morbidity and mortality in people with HIV (PWH). We sought to identify clinical and immunological markers of pulmonary impairment among PWH in India. Methods: Two hundred ten adult PWH receiving antiretroviral therapy (ART) were prospectively evaluated for 3 years. Plasma concentrations of interleukin (IL)-6, IL-10, tumor necrosis factor alpha, D-dimer, C-reactive protein, soluble (s)CD14, and sCD163 were measured at enrollment. We used multivariable linear and logistic regression to measure the association of baseline and time-varying clinical and immunological variables with spirometry-defined chronic obstructive pulmonary disease (COPD), restrictive spirometry pattern (RSP), preserved ratio impaired spirometry (PRISm), forced expiratory volume in 1 second (FEV1), and forced vital capacity (FVC) during the third year of follow-up. Results: After adjusting confounders, females were 7 times more likely to have RSP (95% CI, 2.81 to 17.62; P < .001) and 22 times more likely to have PRISm (95% CI, 7.42 to 69.92; P < .001) compared with men. Higher IL-6 concentrations were associated with lower FEV1 z-scores (β, −0.14 per log-higher; 95% CI, −0.29 to 0.008; P = .06) and higher odds of COPD (adjusted odds ratio [aOR], 2.66 per log-higher; 95% CI, 1.16 to 6.09; P = .02). Higher D-dimer concentrations were associated with lower FVC z-scores (β, −0.40 per log-higher; 95% CI, −0.78 to −0.01; P = .04). Conversely, higher IL-10 concentrations were associated with lower odds of PRISm (aOR, 0.76 per log-higher; 95% CI, 0.59 to 0.99; P = .04). Conclusions: Female sex, higher concentrations of IL-6 and D-dimer, and lower concentrations of IL-10 were associated with pulmonary impairment in adult PWH receiving ART in India.